Fires in nature: a review of the challenges for wild animals - JARA GUTIÉRREZ; Javier de Miguel (European Journal of Ecology, 2021)
Animals living in the wild are exposed to numerous challenges, such as fires, that can lead to suffering. The impacts of fire have been studied in different branches of ecology, but studies of its effects on the welfare of individual animals remain scarce. The current review aims to synthesize a sample of relevant aspects regarding fire’s negative effects on wild animals. We mainly focus on the immediate impacts of fire on individuals. How animals respond to fire depends on many factors including their life history, evolutionary adaptations to fire, and individual stress coping styles, in addition to the characteristics of the fire.